Challenges and Opportunities of Productive Zakat Empowerment in Indonesia: A Literature Review and Problem Tree Analysis - Efendi, Gusri (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
Indonesia holds significant potential for economic empowerment through Productive Zakat as a strategic instrument for poverty alleviation. This study systematically reviews the implementation of Productive Zakat Empowerment in Indonesia, identifies key challenges, and proposes solutions using a Problem Tree Analysis. A total of 358 articles (2020–2025) were initially screened through Google Scholar using Publish or Perish 8, with the 10 most relevant and highly cited articles analyzed in-depth. A mixed-methods approach combining quantitative keyword coding and qualitative causal mapping was applied. Key challenges include ineffective distribution, limited management capacity, lack of mentoring, and uneven access. Recommended strategies include strengthening governance, enhancing transparency, digitalization, and sustained multi-stakeholder collaboration to optimize zakat’s role in socio-economic empowerment.